Diversity-Oriented Approach to Furan Building Blocks and Their Relevance in Organic Synthesis, Materials Science, and Medicinal Chemistry - Kotha, Sambasivarao; Solanke, Balaji U. (Synlett, 2025)
Furan and benzofuran motifs are privileged scaffolds in organic synthesis, and more specifically with relevance in medicinal chemistry, agrochemicals, and materials science. Furan derivatives display diverse biological activities and are frequently employed as key intermediates in the synthesis of complex molecules. This account summarizes recent advances in the synthetic utility of furans, including their functionalization, furan as a 1,3-dicarbonyl equivalent, and furan participation in Diels–Alder transformations to generate benzene derivatives. Particular emphasis is placed on the synthesis of benzofurans via ring-closing metathesis (RCM), a regioselective and atom-economical approach enabled by Grubbs-type catalysts. The utility of RCM for constructing the benzofuran core is illustrated through selected examples, including natural product synthesis and drug-like targets. In essence, this account highlights the strategic value of furan-based molecules and showcases the power of metathesis and the Suzuki-Miyaura (SM) coupling reaction in heterocyclic synthesis.
Keywords: Furan; Benzofuran; Ring-closing metathesis; Suzuki-Miyaura cross-coupling; Claisen rearrangement